Complementary assets of innovative activities: theoretical principles of accounting - V.K. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу, 2023)
The need to expand the current method of accounting for innovative activity of the enterprise, based on the use of modern economic concepts, has been highlighted. The expediency of introducing the concept of complementary assets into the accounting system has been grounded. The historical aspects of the emergence of the concept of «complementary assets» have been analyzed. The concept of complementarity has been characterized and the features of its use in economic sciences have been determined. The need for the development of applied aspects of the accounting of complementary assets, which are used in the innovative activity of the enterprise, have been grounded. The value of accounting information of complementary assets for internal and external users have been disclosed. The main features of complementary assets and their classification according to D.J. Teece approach have been analyzed. The role of complementary assets as the main factor in shaping the technological trajectory of the enterprise has been determined. The essence and importance of complementary assets in ensuring the efficiency of the innovative activity of the enterprise and the need to provide accounting information about them to interested users have been grounded.